Biopharmaceuticals from microorganisms: from production to purification - Angela Faustino Jozala (Brazilian Journal of Microbiology)
ABSTRACT The use of biopharmaceuticals dates from the 19th century and within 5-10 years, up to 50% of all drugs in development will be biopharmaceuticals. In the 1980s, the biopharmaceutical industry experienced a significant growth in the production and approval of recombinant proteins such as interferons (IFN α, β, and γ) and growth hormones. The production of biopharmaceuticals, known as bioprocess, involves a wide range of techniques. In this review, we discuss the technology involved in the bioprocess and describe the available strategies and main advances in microbial fermentation and purification process to obtain biopharmaceuticals.